Juridical Review of the Process of Revoking a Civil Decision Lawsuit Based on Article 271 Rv in Decision Number 413/Pdt.G/2024/PN Mdn" - Kaban, Maria (Ipso Jure, 2024)
Decision number 413/Pdt.G/2024/PN Mdn discusses the legal process for filing a lawsuit based on Article 271Rv. This case involved several parties, with the plaintiff filing to withdraw the lawsuit before the defendant gave an answer. The court stated that the action was in accordance with applicable legal provisions. The process of withdrawing the lawsuit in this case occurred before the lawsuit was read, at which point the judge stated that the withdrawal was not contrary to the law. The judge decided to grant the revocation and ordered the removal of the lawsuit from the register. In the context of Indonesian law, Article 271Rv is the main reference in handling the revocation of the lawsuit. This article allows the plaintiff to withdraw his lawsuit on condition that the withdrawal is carried out before there is a response from the defendant